Factors Associated With Low Levels of Subclinical Vascular Disease in Older Adults: Multi-Ethnic Study of Atherosclerosis - Michos, Erin D. (2009)
Coronary artery calcium (CAC), carotid intimal medial thickness (cIMT), and reduced ankle brachial indices (ABI) are markers of subclinical vascular disease strongly associated with aging. We identified factors associated with low levels of subclinical vascular disease in 1824 participants ≥70 years in the Multi-Ethnic Study of Atherosclerosis. 452 had low CAC (<25(th) percentile), 441 had low cIMT (<25(th) percentile), 1636 had normal ABI (>0.9), and 165 had a combination index indicating favorable values for all three parameters. This combination index was independently associated with younger age [OR=2.5 per 1 SD (95%CI 1.8–3.6)], female gender [OR=3.0(1.9–4.8)], lower BMI [OR=1.6 per 1 SD (1.2–2.0)], absence of hypertension [OR=1.8(1.2–2.6)], absence of dyslipidemia [OR=1.6 (1.04–2.4)], and never smoking [OR=1.7(1.1–2.6)]. No significant associations were observed for C-reactive protein, education, diet, or physical activity. Favorable levels of multiple traditional risk factors, but not several novel risk factors, were associated with subclinical markers of successful cardiovascular aging.